A CMOS Analog Two-Layer Full Signal Range Cellular Neural Network for Image Filtering - Souza de Andrade, Fabian; Cunha, Ana Isabela Araújo; Santana, Edson Pinto; Souza, Ygor Oliveira da Guarda (Symposium on Integrated Circuits and Systems Design (SBCCI); 2020: Anais do XXXIII Symposium on Integrated Circuits and Systems Design, 2020)
This work presents the training and realization of a CMOS analog two-layer FSR CNN obtained through the extension of an existing one-layer version. A genetic algorithm has been developed for the learning process and has been applied to the determination of templates parameters in a gray-scale image filtering task. Networks implementing first order Butterworth spatial filters have been simulated and the results are compared to its ideal model and FFT computations; allowing to validate the proposed learning process and circuit applicability.